Mean Blood Loss in Third Stage of Labour Treated with and without Prophylactic Tranexamic Acid - Hafiza Naveeda Khurshid, Samar Noor, Huma Tasheen, Shabana Khokar, Sobia Saleem (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Massive obstetrical hemorrhage, a leading contributor towards maternal fatality in economically developing countries, is occasionally related with the passive and apathetic management of the third stage of labor. The increasing frequency of anaemia among pregnant women in developing countries, mild to moderate blood loss during labour necessitates massive transfusions with associated complications. Aim: Recent studies claimed that prophylactic tranexamic acid can significantly reduce the mean blood loss during 3rd stage of labour and advocated it in future practice. Methods: The research was conducted as randomized controlled trial carried out from February 2021 to October 2021 in the Department of Diagnostic Radiology and Obstetrics & Gynaecology Department, Ganga Ram Hospital, Lahore. A total of 116 pregnant women aged between 18-35 years presenting in labor at term (37-42 weeks of gestation as per dating scan) which were randomly allocated into two groups. Patients in Group-A were given additional tranexamic acid at the end of 2nd stage of labor while those in Group-B received conventional treatment alone. Results: Patients were 28.33±4.77 years with the mean age while the mean gestational age at delivery was 39.39±1.69 weeks. 30(25.9%) women were primiparas and 86 (74.1%) were multiaparas. The mean BMI of these patients was 27.50±3.90 Kg/m2 while the average duration of 3rd stage of labor was 4.69±1.83 minutes. Patients taking prophylactic tranexamic acid lost significantly less blood in the third stage of labors than controls (244.83±21.47 vs. 354.09±22.36 ml; p-value<0.001). Conclusion: In the present study, prophylactic tranexamic acid was found to significantly reduce the mean blood loss during 3rd stage of labor which along with low cost, widespread availability and oral administration advocates the routine use of tranexamic acid (during 3rd stage of labor) in future obstetric practice to minimize blood loss with subsequent decreased need for blood transfusion and better patient’s recovery.